Designing an academic self-regulatory model based on basic psychological needs and family communication model mediated by positive adolescent development and Academic Aspiration - Abdolmaleki, Shahriar; Pirani, Zabih; Zanganeh, Firozeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Many factors are involved in the academic success of students, and academic self-regulation is one of them. Academic self-regulation can be an influencing variable on academic progress and prevention of academic failure, and it has been the focus of many researchers in recent years. Therefore, this research was conducted with the aim of examining the fit of the academic self-regulation model based on the basic psychological needs and the family communication model with the mediation of positive adolescent development and academic enthusiasm. Methods: This study was a descriptive correlational study. The statistical population included male high school male students in the city who were selected by cluster sampling from 420 students and with the standard scale of satisfying basic psychological needs Ganyeh (2003), revised questionnaire of communication patterns of Koerner and Fitzpatrick family (2002), self-administered questionnaire. Savari and Arabzadeh (2013), Goldoff et al. (2014) Adolescent Positive Development Questionnaire and Shuffle et al.'s (2002) Academic Achievement Questionnaire were evaluated. Data were analyzed using Smart PLS3 statistical software. Results: The findings indicated that the positive development of adolescence and academic aspiration play a mediating role between academic self-regulation based on basic psychological needs and family communication pattern (P